Digitalization need: Green promotion framing in reinforcing the revenue increase - I Wayan Suwastana; Dewa Made Suria Antara; Nyoman Mastiani Nadra; Ni Kadek Herna Lastari (Journal of Applied Sciences in Travel and Hospitality, 2023)
The current trend among tourists is staying in an accommodation that has applied the principles of green or pro-environment in the operations. Manah Shanti Resort has conducted green promotion to attract tourists who know about tourism sustainability well. The study aimed at identifying the strategies that are possible to apply to have better promotion in improving hotel revenue. The study used qualitative research design. The data were collected by conducting FGD with the owner, management staff, and operational team, interviews, and document reading initiations. Besides, the data obtained were determined in the SWOT analysis table of the green promotion yielding IFAS and EFAS data analysis. The resort generates revenue effectively as a result of green promotion performance. However, the resort partly implements green promotion and is categorized in a growth stage. According to the analysis, there are eight strategies suggested and categorized as Strengths-Opportunities, Weaknesses-Opportunities, Strengths-Threats, and Weaknesses-Threats strategies to conduct better green promotion in increasing revenue. Thus, further actions need to be taken to optimize the green promotion at Manah Shanti regarding digitalization needs.